Provider Initiative HIV Testing And Counseling (PITC) Skills At Public Health Centers In Rural And Urban Areas - Hikmah, Faiqatul; Notobroto, Hari Basuki; Devy, Shrimarti Rukmini; Susindra, Yoswenita; Kartika, Ria Chandra; Ramadhaniah (Universitas Airlangga, 2025)
Improving the quality of HIV testing services in public health centers must be supported by the knowledge of HIV that health worker professionals must have. In PITC services, the ability of health professionals to build relationships is crucial to establishing trust and good communication with patients. Providing information about HIV will help patients make decisions about their health status. However, the PITC services provided by health workers are less than satisfactory. Aims: This study aims to analyze the factors associated with the PITC skills of health professionals at Indonesian public health centers in urban and rural areas. Methods: Observational design with a cross-sectional approach was used in this research. The sample in this study involved 120 health worker professionals, including nurses, doctors, and midwives, who implemented HIV testing, who were selected using simple random sampling based on the location of their health center. The data were analyzed using multigroup analysis in SmartPLS 3 Result: The knowledge of HIV positively influenced the capability of health professionals to assess HIV risk factors and PITC skills (p = 0.011). The capability of health professionals to determine HIV risk factors also positively influenced PITC skills(p = 0.000). In addition, the ability of health professionals to build relationships with patients positively influenced PITC skills(p = 0.000). Conclusion: Different variables affect health professionals' PITC skills compared to rural and urban health professionals. Learning a language that the patient understands is highly recommended in providing good service during a HIV test.